(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
Background: Re-performing an emergency operation after a surgical time is something that not only shows a type of failure of the first surgery but also gives high anxiety in patients who are reoperated (Dillstro, Bjersa, & My, 2016). The reason for these reoperations are seen due to multiple factors that occur during and after the laparoscopic surgeries performed (Tae Kwan, et al., 2019). Its early identification is imperatively necessary since this would prevent multiple complications, high hospital costs and a possible increase in deaths in the operating room (Xiao, Wang, Quan, & Ouyang, 2018). Objective: To identify the most significant risk factors that precede surgical reoperations in abdominal surgery. Materials and methods: Statistical data was collected from the Abel Gilbert Ponton Hospital patients. The Excel program was used to carry out the statistics and obtain “P” plus “OR” and corroborate statistical significance between the risk factors investigated. Results: Two groups with different populations were taken (Group A: 860 and Group B: 109) which were subdivided into female and male (Group A: male: 501; female: 359; Group B: male: 61; female : 48). It was evidenced that the male gender had a higher prevalence of emergency abdominal reoperations in 58.3% and 56.0% respectively. The main postoperative complications that existed in reintevered patients were surgical site infections (46.8%), intra-abdominal collection (26.6%) and septic shock (24.8%). There were also significant statistical figures in comorbidities (glycemia and arterial hypertension), surgical time and values in blood chemistry. Conclusions: more studies are needed in Ecuador that reveal more kinds of risks presented by suddenly reoperated patients in order to make them known and therefore reduce their incidence.